(untitled) (Research, Society and Development, 2020)
Baccharis dracunculifolia, native to Brazil and the main source of “green propolis”, has been reported with several biological activities, and may be a source of bovine tick control substituting synthetic acaricides. Objective: to evaluate the in vitro and ex situ acaricidal activity of B. dracunculifolia leaf and flower essential oils against Rhipicephalus microplus. Methodology: the essential oils were extracted by hydrodistillation and analyzed by a gas chromatography coupled to mass spectrometry; the acaricidal activity of the essential oil was evaluated in vitro against adult females and against the egg hatchability; moreover, the acaricidal activity against tick larvae was evaluated in vitro and ex situ. Results: the major class of the essential oils was oxygenated sesquiterpene (55.1% leaves 50.4% flowers) and the main compounds were (21.5% leaves; 20.6% flowers) and spathulenol (21.8% leaves; 20.3% flowers). The essential oil at 500 mg/mL was effective to control egg hatchability with a reduction of egg laying capacity and decrease of number of adult ticks and larvae. The larvicidal activity of the essential oil had LC99.9 from 35 to 37 mg/mL by probit analysis, and the essential oil from 11 to 14 mg/mL presented 85 to 95% of treatment efficiency in the ex situ test. Conclusion: B. dracunculifolia leaf and flower essential oils are stable and have application potential to control bovine ticks.